(untitled) (Journal of Applied Learning and Teaching, 2020)
The use of computing technologies in human learning is rapidly growing and advancing in various fields of learning and training. Virtual reality (VR) is one of the growing computer techniques used in schools and training institutes to help improve students’ learning experience, create an interactive environment and build students’ confidence while working in a physical environment. The benefits of using virtual reality are yet to be fully explored in all fields of endeavour. Virtual reality has been applied in the field of medicine for rehabilitation of patients and in training of medical students. In addition, it has been used in operations management, manufacturing processes and design as well as in the aviation industry for the dissemination of safety information, and maintenance. VR holds great and promising prospects in education, tourism, entertainment, and architecture. Hence, this paper presents a review of the trends of applications of virtual reality technologies, its potentials and prospects for learning in various fields.